Importancia del uso de azufre en el cultivo de palma aceitera (Elaeis guineensis Jacq) - Campos Banchen, Aurora Jamileth (2024)
This document addressed the topic Importance of the use of sulfur in the cultivation of oil palm (Elaeis guineensis Jacq). Its multifaceted importance in healthy plant development sulfur plays a crucial role in the cultivation of oil palm (Elaeis guineensis). However, sulfur is an essential component in protein synthesis, which contributes to the structural and functional growth of oil palm. The main objective is. Determination of each of the qualities of the use of this element, which is sulfur in the oil palm (Elaeis guineensis). The development of different crops, however, can be affected, for different reasons, often in a more serious way. Early recognition of symptoms and proper management of sulfur conditions are essential to ensure healthy growth and optimal development of African palm nurseries. I carried out the methodology using information from analysis techniques, magazines, blogs, current texts, online articles, synthesis, collecting information from updated data. The results obtained are that the symptoms of sulfur deficiency in oil palm can manifest themselves in various ways, with one of the most obvious indicators being the discoloration of the leaves. In early stages, the leaves may have a pale yellowish tone, especially in the youngest parts of the plant. However, it is recommended that improving soil quality helps maintain soil pH at optimal levels, which favors the availability of other essential nutrients for the growth of oil palm.